The Implementation of Minimum Service Standards (MMS) on Public Service for Health Services Sector in Bondowoso, Indonesia - Untung Kuzairi; Hary Yuswadi; Agus Budihardjo; Himawan Bayu Patriadi (Otoritas : Jurnal Ilmu Pemerintahan, 2018)
One of heatlh policies implemented by the hospital is the minimum service standards (MSS). MSS is a benchmark of hospital service quality in providing services to the public. Talking about health service quality problem, it was found out as the field fact that the achievement of MSS indicator in General Hospital of Dr. H. Koesnadi Bondowoso, Indonesia in 2016 still did not fulfill target of standard hospital service (type B) and  minimum service standard (MSS) of hospital. This fact shows that the quality of health services in general hospital of  dr. H. Koesnadi Bondowoso is still low. So, this research aims to describe the policy implementation of minimum service standard and to analyze the obstacles in the implementation of MSS policy at general hospital of  dr. H. Koesnadi Bondowoso. So, this research would discuss the policy implementation of minimum service standards by using Edward III concept as a tool to analyze it. This research employed qualitative research with phenomenological approach. The results showed that the implementation of MSS policy of dr. H. Koesnadi Bondowoso general hospital still did not run well. This was due to several factors  such as communication, bureaucratic structure, sources, dispositions (attitude) and leadership in sectoral ego control. Sectoral ego can be shaped from educational background of specialist doctors who still adhered seniority and lack of individual role of implementor in building interpersonal communication and conflict management.